High expression of MRE11 correlates with poor prognosis in gastric carcinoma - Junqing Li; Taiqiang Su; Liang Yang; Changhua Zhang; Yulong He (BMC, 2019)
Abstract Background MRE11, a protein known to play a vital role in DNA double-strand break repair, is associated with the prognosis of a variety of tumours, but there are few studies regarding the role of MRE11 in gastric carcinoma (GC). The present study aimed to explore the clinicopathological significance and prognostic value of MRE11 expression in GC. Methods Data from the TCGA, GEO and Oncomine databases were analysed to assess MRE11 mRNA levels in GC. The prognostic role of the level of MRE11 mRNA was examined via the Kaplan-Meier plotter. MRE11 protein expression in tumour tissues from 155 GC patients was analysed by immunohistochemistry. Relationships between MRE11 expression and clinicopathological characteristics, overall survival (OS) and recurrence-free survival (RFS) were evaluated by Cox proportional hazards regression models and Kaplan-Meier survival curves. Results The results of bioinformatics analysis showed that MRE11 mRNA levels in GC tissues were higher than those in normal tissues (P < 0.01). Tissue microarray analysis showed that MRE11 protein expression was increased in GC tissues (P < 0.001), and MRE11 overexpression in GC tissues was significantly related to lymph node metastasis (P < 0.05), distant metastasis (P < 0.05) and tumour-node-metastasis stage (P < 0.05). Kaplan-Meier analyses showed that patients with GC who exhibited MRE11 overexpression had worse OS and RFS. According to Cox proportional hazards analyses, MRE11 overexpression was an independent prognostic factor for OS and RFS in these GC patients. Conclusions MRE11 overexpression is significantly associated with poor prognosis, and MRE11 may serve as a prognostic biomarker in GC patients.